Blasius and Sakiadis slip flow of H2O–C2H6O2 (50:50) based nanoliquid with different geometry of boehmite alumina nanoparticles - N. Vishnu Ganesh; Qasem M. Al-Mdallal; K. Reena; Sidra Aman (Case Studies in Thermal Engineering, 2019)
The geometry of the nanoparticles in nanoliquids has significant influence in many engineering and bio medical applications and also the classical flow problems such as Blasius and Sakiadis problems are important in industrial applications. In view of this, an investigation on the flow of H2O–C2H6O2 (50:50) mixture based nanoliquid with different geometry of boehmite alumina nanoparticles is carried out in the presence of viscous dissipation effects. Spherical, blades, bricks, platelets and cylindrical geometries of the nanoparticels are considered. Both Blasius and Sakiadis flow types are analysed for slip and no-slip cases. The thermal and velocity slip boundary conditions are included as a function of nanoparticle volume fraction. Mathematical model is solved numerically by the Iterative Power Series (IPS) method and shooting strategy with the thermo-physical properties of different geometries nanoparticles. It is observed that the thermal boundary layer thickness is increased for cylindrical nanoparticles and decreased for spherical nanoparticles in both slip and no-slip cases of Blasius and Sakiadis flows. The reduced Nusselt number is increased with nanoparticle volume fraction for all shapes of boehmite alumina nanoparticles except spherical nanoparticles. Keywords: Blasius flow, Nanofluid, Sakiadis flow, Viscous dissipation, Slip flow